Surgical hernia- Treatment - Prothesis lmplantation - Croci, Fabio; Gastambide, Carmelo; Cordal, Adriana; Pérez Penco, Ernesto; Terra, Eneas (Cirugía del Uruguay, 1984)
In many cases even trations are a problem of no easy solution, either due to their characteristics, volu• me, seat of the defect or the area where they are set. Between an 8 and 10% of conventional repairing are a failure. Substitution prothesis implantation is in many cases necessary not only fr.om the anatomical but also from the functional point of view. 48 cases of implanta• tion are analyzed in this comm unication, and results evaluated.